Protective Effects of Magnesium Glycyrrhizinate on Methotrexate-Induced Hepatotoxicity and Intestinal Toxicity May Be by Reducing COX-2 - Cao, Yuzhu; Shi, Hang; Sun, Zhiguang; Wu, Jiawei; Xia, Yawen; Wang, Yufei; Wu, Yuanyuan; Li, Xiaoman; Chen, Wenxing; Wang, Aiyun; Lu, Yin (Frontiers in Pharmacology, 2019)
Magnesium isoglycyrrhizinate (MgIG), which has been widely employed to treat chronic hepatitis, is synthesized from 18-β glycyrrhizic acid, a main component of traditional Chinese medicine Glycyrrhiza uralensis Fisch. Although the protective effects of MgIG on methotrexate (MTX)-induced liver toxicity have been well-documented, the underlying mechanism remains elusive. MTX was initially used to treat pediatric acute leukemia, and has been widely applied to psoriasis therapy. However, its clinical applications are limited due to hepatotoxicity and intestinal toxicity. Herein, prophylactic administration of MgIG (9 and 18 mg/kg/day) significantly reduced the levels of aspartate aminotransferase and alanine aminotransferase in the serum of rats receiving intravenous injection of MTX (20 mg/kg body weight). MgIG also attenuated MTX-induced hepatic fibrosis. Moreover, it better protected against MTX-induced hepatocyte apoptosis and decreased the serum level of malondialdehyde than reduced glutathione (80 mg/kg/day) did. Interestingly, MTX-induced cyclooxygenase-2 (COX-2) expression, intestinal permeability and inflammation were attenuated after MgIG administration. In addition, MgIG (9 and 18 mg/kg) reduced MTX-induced colocalization of zonula occludens-1 (ZO-1) and connexin 43 (Cx43) in intestinal villi. In conclusion, MgIG exerted beneficial effects on MTX-induced hepatotoxicity and intestinal damage, as a potentially eligible drug for alleviating the hepatic and intestinal side effects of MTX during chemotherapy.